Does storytelling add value to fine Bordeaux wines? - Pierre Mora; Florine Livat (Wine Economics and Policy, 2013)
Purpose: The purpose of this paper is to understand if the use of a vineyard's storytelling helps to better understand the position of each vintage in a niche and luxury market. Two main objectives structure this article: discovering what criteria constitutes the narratives of corporate communications of the Grand Crus market on the first hand and to studying the positioning of the different communications styles depending on the designation of origin on the other hand. Methodology: The methodology of this research is based on a lexicographic analysis of the corporate communications of the 132 chateaux members of the Union des Grands Crus. Findings: The results show that 13 components form the basis of the narratives. According to the appellations of origin, four main styles of communication can be identified. The research also shows a link between the price level of the wine and the style of the corporate storytelling. Originality/value: There has been a strong increase in the price of Grands Crus from Bordeaux in recent years. The price increase is not explained by the objective value of these products but rather their symbolic position and image evoked of a world of luxury. Moreover, it seems that these images generate little differentiation among wine brands, while they all claim that they are unique.
Keywords: 330; Communication styles; Price; Semantics; Storytelling; Wine